COLOPHON AS A SOURCE ON THE ARABIC MANUSCRIPT TRADITION OF DAGESTAN - Alibekov, Hizri Gadzievic (History, Archeology and Ethnography of the Caucasus, 2024)
This article deals with the study of the Dagestan handwritten tradition through an examination of colophons found in Arabic and Arabographic manuscripts produced by Dagestanis between the 16th and 20th centuries. The author examined colophons of Arabic manuscripts stored in various public and private collections throughout Dagestan. The process of copying a manuscript often involved the scribe checking their work against the original text (protograph) and other manuscripts. The quality of the final handwritten book depended significantly on both the quality of the protograph and the availability of other manuscripts for collation. Colophons sometimes contain information recorded by the scribe concerning the copying process, the circumstances surrounding the creation of the manuscript, the protograph used, and any other manuscripts consulted during the copying process. Thus, the colophon is an important and valuable historical source that sheds light on numerous aspects of Arab-Muslim written culture in Dagestan. Information detailing the process of copying manuscripts appears in Dagestan colophons around the end of the 17th century, which coincides with a qualitative leap in the Arabic manuscript tradition and Muslim education during this period. This phenomenon can be associated with a new stage of Islamization in Dagestan, which began in the 17th century and involved a deepening of Islamic influence. As a result, the number of madrasas – Muslim spiritual and educational centers – increased significantly during this period. These madrasas, which became the primary places for manuscript copying, relied on high-quality educational materials in the form of reliable copies of Arabic manuscripts on various Muslim disciplines.